DETERMINATION OF DENGUE VIRAL INFECTION SEVERITY IN PEDIATRIC BASED ON PHYSICAL EXAMINATION AND LABORATORY TESTS: A CASE STUDY OF A 7 MONTHS OLD BABY WITH DENGUE HAEMORRHAGIC FEVER - Muhammad Ghaza Syahputra; Ayu Anggraini Kusumaningrum; Dewi Apriani; Dimas Tri Anantyo (Faculty of Medicine, Diponegoro University, Semarang, Indonesia, 2020)
Background: Dengue viral infection can infect people of all ages, including infants less than 1-year-old. The Disease severity of dengue infection consists of asymptomatic infection and symptomatic infection. The symptomatic infection has varying degrees of severity: undifferentiated fever, dengue fever, DHF, and Dengue Shock Syndrome (DSS). Method: The data obtained by interviewing the patients' parents for the symptoms and patients' medical records for information on the treatments and examinations. Case: A 7 months old baby arrived at the hospital with a continuous abrupt 3 days fever, the condition is accompanied by watery stool two times a day, vomiting once a day. Discussion: The patient arrived at the hospital with a continuous abrupt 3-day fever. The results of the physical examination showed a positive tourniquet test and palpable liver. The laboratory test results showed that the patient has thrombocytopenia, and the chest x-ray results showed that the patient has pleural effusion. Conclusions: The patient was diagnosed with DHF without shock and sent home after the patient got fluid therapy, supportive, and symptomatic treatments.